Ushul Ibn Hazm (Comparison Study between Ushul Ibn Hazm And Ushul of the Four Imams) - Nugraha, Iqbal Subhan, Dr.Muindinillah Basri, M.A (2013)
There is no difference opinion tells about this statement that Imam Ibn Hazm is an Ulama and a Mujtahid who has real different opinion with the four imams: Abu Hanifah, Malik, Syafi'I, and Ahmad. The causal factor of the difference is their ushul. The writer tries to compare the ushul characteristic and what the affect to the fiqh of Islam. In this study, the writer uses comparative method. This paper was written truly and uses trusted sources as the reference. As the result, the writer finds the difference and similarity between USHUL IBN HAZM and USHUL of the Four Imams and the affect to fiqh of Islam.